Feminism, citizenship and social activity: the role and importance of local women's organisations, Nottingham 1918-1969 - Clements, Samantha Ruth (2008)
This local study of single-sex organisations in Nottingham and Nottinghamshire is an attempt to redress some of the imbalanced coverage given to this area of history thus far. A chronological study, it examines the role, importance and, to some extent, impact of a wide range of women's organisations in the local context. Some were local branches of national organisations, others were specifically concerned with local issues. The local focus allows a challenge to be made to much current thought as to the strength of a "women's movement" in the years between the suffrage movement and the emergence of a more radical form of feminism in the 1970s. The strength of feminist issues and campaigning is studied in three periods -- the inter-war period, the Second World War and its immediate aftermath, and the 1950s and 1960s. The first two periods have previously been studied on a national level but, until recently, the post-Second World war era has been written off as overwhelmingly domestic and therefore unconstructive to the achievement of any feminist aims. This study suggests that, at a local level, this is not the case and that other conclusions reached about twentieth century feminism at a national level are not always applicable to the local context.